May–Thurner syndrome causing deep vein thrombosis in the postoperative patient - L., Ashwini Vishalakshi; V., Meenakshi; Ganesh, Amritha; P., Pallavee (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
May–Thurner syndrome is a rare cause of left iliac deep vein thrombosis due to an anatomical variant in which right common iliac artery overlies and compresses left common iliac vein against lumbar spine. Patients with May–Thurner syndrome usually present in their 2nd to 4th decade of life. Pregnancy and intra-abdominal surgeries are known precipitating factors in acute May–Thurner syndrome. We report the case of a woman in her 3rd decade of life who presented with May–Thurner syndrome following total abdominal hysterectomy. This case report hopes to bring attention to the high variant of patient population with May–Thurner syndrome and the necessity for surgical intervention of stent placement to prevent recurrence.